2012
DOI: 10.1038/cddis.2012.190
|View full text |Cite
|
Sign up to set email alerts
|

Grainyhead-like 2 (GRHL2) inhibits keratinocyte differentiation through epigenetic mechanism

Abstract: We recently identified Grainyhead-like 2 (GRHL2), a mammalian homolog of Grainyhead in Drosophila, to be a novel transcription factor that regulates hTERT gene expression and enhances proliferation of normal human epidermal keratinocytes (NHEK). In the current study, we show that GRHL2 impairs keratinocyte differentiation through transcriptional inhibition of the genes clustered at the epidermal differentiation complex (EDC), located at chromosome 1q21. Gene expression profiling and subsequent in vitro assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 39 publications
6
60
1
Order By: Relevance
“…We further showed that Grhl2 knockdown in the alveolar type II-like MLE15 cell line resulted in cell-flattening events, with alteration in distribution of F-actin filaments. Moreover, we also suggested that the expression of Tert, which is an important injury repair gene, may be regulated by Grhl2 in alveolar epithelium, which corroborates another study showing that GRHL2 mediates epigenetic regulation of TERT in human keratinocytes (5,6,19). The fact that mutation in TERT is known to predispose to familial IPF (1,22,38) suggests a possible functional role of GRHL2 in the pathogenesis of IPF.…”
supporting
confidence: 88%
“…We further showed that Grhl2 knockdown in the alveolar type II-like MLE15 cell line resulted in cell-flattening events, with alteration in distribution of F-actin filaments. Moreover, we also suggested that the expression of Tert, which is an important injury repair gene, may be regulated by Grhl2 in alveolar epithelium, which corroborates another study showing that GRHL2 mediates epigenetic regulation of TERT in human keratinocytes (5,6,19). The fact that mutation in TERT is known to predispose to familial IPF (1,22,38) suggests a possible functional role of GRHL2 in the pathogenesis of IPF.…”
supporting
confidence: 88%
“…GRHL2 is a transcription factor playing roles in development, regulation of epithelial mesenchymal transition (EMT), and restoring the sensitivity to anoikis (27 ). GRHL2 overexpression was detected in several cancers; however, in certain subclasses of breast cancer, GRHL2 was downregulated (27,28 ). This dual, context-dependent effect of GRHL2 might be explained by operation through transforming growth factor ␤ (TGF-␤) signaling, which also has both tumorpromoting and -suppressing effects in a contextdependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…GRHL2 directly regulates genes that are essential for epithelial fate, such as those encoding E-cadherin (cadherin 1), claudin 3 and claudin 4 (Mostov et al, 2012;Werth et al, 2010), and other epithelial genes are downregulated in Grhl2 loss-of-function embryos (Pyrgaki et al, 2011). Despite the knowledge of these and other (Chen et al, 2012;Gao et al, 2013;Walentin et al, 2015) GRHL2-regulated downstream processes, it remains to be determined how Grhl2 loss in the NNE leads to failure of NTC. Thus, continuing studies of GRHL2 function could shed light on the molecular processes that underlie NNE-driven NTC.…”
Section: Introductionmentioning
confidence: 99%